E-commerce and digital marketing in times of Covid-19. Analysis in a peruvian private company - Soler Grillo, Sonia Francisca (2021)
One of the great challenges for private sector companies in the Covid-19 pandemic is to understand the behavior of electronic commerce, since in this way they will be able to obtain improvements in their economy, making use of advertising media to be able to expand the level of sales and customer visits, rather, improve your digital marketing. This study seeks to determine if electronic commerce influences digital marketing in a private company in Peru. The approach was quantitative, applied type. The population was represented by 1200 clients and the sample by a total of 291. The data collection technique was the survey and the instrument the questionnaires. The results showed that electronic commerce and digital marketing have a regular level, due to the fact that actions related to this medium are rarely taken. It was concluded that electronic commerce influences the improvement of digital marketing, understanding that when the analyzed private company takes into account in its policies to make use of these tools, it will obtain satisfactory indicators in the acquisition of clients and therefore in the level of sales.